A Novel Two-Step Approach for Retrieval of an Impacted Biliary Extraction Basket - Calvin H. Y. Chan; Fergal Donnellan; Godfrey C. K. Chan; Michael F. Byrne (Case Reports in Gastrointestinal Medicine)
Biliary extraction baskets are a commonly used instrument for the removal of choledocholithiasis in endoscopic retrograde cholangiopancreatography (ERCP). Impaction of the extraction basket is a recognized complication of ERCP, and is usually the result of discrepancy between the size of bile duct stone and the diameter of the distal bile duct. Whilst mechanical lithotriptors can be used to crush the stone or break the wires of the basket to allow its release, failure of the lithotriptor device can occur. We describe the case of a 59-year-old gentleman who had an ERCP performed for choledocholithiasis. Basket impaction was encountered, and the mechanical lithotriptor failed to dislodge the stone/basket complex. A two-step technique involving balloon dilatation and forceps manipulation of the basket was applied to successfully dislodge the impacted basket. We believe this simple and safe technique should be adopted to rescue impacted biliary extraction baskets to avoid the need for potential surgical removal.